Alkaline-assisted Microwave Pretreatment of Tetraselmis suecica Biomass for Fed-batch Enzymatic Hydrolysis - Mohd Asyraf Kassim; Tan Kean Meng; Noor Aziah Serri (Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
A two-part study on pretreatment and fed-batch enzymatic hydrolysis of pretreated Tetraselmis suecica using a high initial biomass concentration was conducted. First, the effect of different pretreatment processes, i.e. microwave (MC), dilute alkaline (AK), and microwave-alkaline assisted (MAK) pretreatment, on enzymatic hydrolysis of T. suecica biomass was evaluated. Furthermore, high initial biomass concentration enzymatic hydrolysis improvement via a fed-batch strategy was performed. Among the pretreatments tested, the MAK pretreatment produced the highest sugar concentration at 9.83 ± 0.24 mg/mL, corresponding to a conversion yield of up to 85.58% of carbohydrate content available in the pretreated biomass. The solid fraction generated after pretreatment was characterized using Fourier transform infrared (FTIR) spectroscopy. The FTIR analysis revealed a significant change in the functional hydroxyl and acetyl groups of the biomass, which is favorable for enzymatic hydrolysis. Introducing an initial microalgal biomass concentration beyond 15% (w/v) exhibited a low enzymatic hydrolysis yield. The fed-batch enzymatic hydrolysis strategy of the MAK pretreated T. suecica was further investigated by adding the substrate at different time intervals. The findings indicate that the fed-batch operation system could enhance sugar production and enzymatic hydrolysis yield one-fold.